Enhancing visible luminescence in sprayed-ZnO nanostructure through Cu doping - Fatima Zohra Bedia; Asma Bedia; Sidi Mohammed Bedia; Nabila Maloufi; Michel Aillerie; Khadidja Rahmoun (AIP Advances)
Cu-doped ZnO (CZO) is a low-cost, oxide-friendly material synthesized in various ratios (0%, 1%, 2%, and 3%) via spray pyrolysis on a glass substrate at 350 °C. SEM images revealed that the CZO films consist of aggregated spherical nanoparticles, each with a diameter of less than 20 nm. XRD and Raman measurements confirmed that the CZO thin films exhibit a polycrystalline wurtzite structure with a preferential 101̄1 orientation. The role of defects influencing the luminescence behavior of CZO films in the visible spectrum was investigated. Increasing the Cu content in ZnO crystals enhanced and produced four distinct color emissions in the visible photoluminescence spectrum: blue, green, yellow, and red. This rare occurrence in sprayed ZnO films is attributed to various defects, with the most prominent one being oxygen vacancies (Vo+–Vo++), zinc interstitials (Zni), and oxygen interstitials (Oi). Notably, the defects significantly decreased with the addition of 2 at. % Cu, unequivocally linked to the emergence of Zn vacancies (VZn). An increase in defects in the ZnO crystal leads to bandgap narrowing, from 3.273 to 3.202 eV. This study demonstrates that CZO films, synthesized through a cost-effective and straightforward method, are well-suited for optoelectronic applications.